The Degree of Effectiveness of The New Teachers Program in Applying Modern Teaching Strategies for Teachers in The First Three Grades - Al- Kasasbeh, Mays Khaled; Ibdah, Alaa Fareed (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the degree of effectiveness of the new teachers’ program in applying modern teaching strategies for teachers in the first three Grades In Government Schools of the second Amman Directorate. the study sample consists of (15) male teachers and (171) female teachers. To achieve the objectives of the study, a questionnaire was used as a tool for data collection; it consisted of (21) paragraphs. The result showed that the degree of effectiveness of the new teachers’ program in applying modern teaching strategies for teachers in the first three Grades was moderate with (3.65) score. The finding also showed there were statistically significant differences between the level of applying modern teaching strategies refers to their teaching experience in favor of (6 years and more) besides there wasn’t statistically significant differences between the level of applying modern teaching strategies refers to their qualifications. In light of these result, the researcher recommended a set of recommendation the most of these was the need to pat attention to the professional preparation of the first three classroom teachers and to provide appropriate educational means for using modern teaching strategies.